3D biocomposites comprising marine collagen and silica-based materials inspired on the composition of marine sponge skeletons envisaging bone tissue regeneration - Martins, Eva (2022)
Ocean resources are a priceless repository of unique species and bioactive compounds with denouement properties that can be used in the fabrication of advanced biomaterials as new templates for supporting the cell culture envisaging tissue engineering approaches. The collagen of marine origin can be sustainably isolated from the underrated fish processing industry by-products, while silica and related materials can be found in the spicules of marine sponges and diatoms frustules. Aiming to address the potential of biomaterials composed from marine collagen and silica-based materials in the context of bone regeneration, four different 3D porous structure formulations (COL, COL:BG, COL:D.E, and COL:BS) were fabricated by freeze-drying. The skins of Atlantic cod (Gadus morhua) were used as raw materials for the collagen (COL) isolation, which was successfully characterized by SDS-PAGE, FTIR, CD, and amino acid analyses, and identified as a type I collagen, produced with a 1.5% yield and a preserved characteristic triple helix conformation. Bioactive glass 45S5 bioglassÂ® (BG), diatomaceous earth (D.E.) powder, and biosilica (BS) isolated from the Axinella infundibuliformis sponge were chosen as silica-based materials, which were obtained as microparticles and characterized by distinct morphological features. The biomaterials revealed microporous structures, showing a porosity higher than 85%, a mean pore size range of 138â 315 Âµm depending on their composition, with 70% interconnectivity which can be favorable for cell migration and ensure the needed nutrient supply. In vitro, biological assays were conducted by culturing L929 fibroblast-like cells, which confirmed not only the non-toxic nature of the developed biomaterials but also their capability to support cell adhesion and proliferation, particularly the COL:BS biomaterials, as observed by calcein-AM staining upon seven days of culture. Moreover, phalloidin and DAPI staining revealed well-spread cells, populating the entire construct. This study established marine collagen/silica biocomposites as potential scaffolds for tissue engineering, setting the basis for future studies, particularly envisaging the regeneration of non-load-bearing bone tissues.